Rural innovation systems and networks: Findings from a study of Ethiopian smallholders - Spielman, David J.; Davis, Kristin E.; Negash, Martha; Ayele, Gezahegn (International Food Policy Research Institute, 2008)
Agriculture in Ethiopia is changing. New players, relationships, and policies are influencing how smallholders access and use information and knowledge. Although this growing complexity suggests opportunities for Ethiopian smallholders, too little is known about how these opportunities can be effectively leveraged to promote pro-poor processes of rural innovation. This paper examines Ethiopia's smallholder agricultural sector to provide qualitative insights into the interactions between smallholders and other actors in the agricultural sector and the contribution those interactions make to the smallholders' innovation processes. Case studies of smallholder innovation networks in 10 communities suggest that public sector extension and administration exert a strong influence over smallholders' access to knowledge and information relative to market or civil society actors. Given the priority the Ethiopian government has placed on improving rural welfare by increasing market access among smallholders, the findings of this study may suggest the need to further explore policies and programs that create more space for market and civil society actors to participate in smallholder innovation networks.